Micro-affordance: the potentiation of components of action by seen objects. - Ellis, Rob; Tucker, Mike (British Journal of Psychology, 2000)
It is suggested that seen objects potentiate a range of actions associated with them, irrespective of the intentions of the viewer. Evidence for this possibility is provided by the data from two experiments, both of which required a participant to make a binary motor response to an auditory stimulus. In the first experiment the response was a power or precision grip, which was performed whilst simultaneously viewing a real object which would normally be grasped using either a power or precision grip. A significant interaction of response and grip compatibility of the object was observed. Similar results were obtained in the second experiment when a wrist rotation of a given direction was used as a response, whilst viewing objects which would require wrist rotations if they were to be grasped. The effects of the seen objects on components of action are described as micro-affordances which are said to be dispositonal states of the viewer's nervous system. Reprinted by permission of the publisher.